Pemanfaatan Sekam Padi Menjadi Briket Ramah Lingkungan untuk Mendukung Energi Berkelanjutan di Desa Tanjung Baik Budi Kabupaten Ketapang: Empowering Local Farmers through Waste-to-Energy Innovation - Desyana Ghafarunnisa; Syarifah Aqla; Firman; Sartika; Sy Indra Septiansyah; Maya Santi; Herman; Idris Herkan Afandi; Syarifah Mastura (Journal of Applied Community Engagement, 2025)
Tanjung Baik Budi Village has great potential in rice production, yet faces challenges with unmanaged rice husk waste, which is often burned openly, causing pollution and resource inefficiency. This community service program aims to train and assist local residents in transforming rice husk into eco-friendly briquettes as an alternative, sustainable energy source. The method includes socialization, technical training, production assistance, and evaluation. The briquette-making process involves carbonization, charcoal grinding, mixing with natural adhesives, molding, drying, and packaging. The results show increased community skills in producing briquettes and enthusiasm for developing alternative energy-based enterprises. Rice husk briquettes are proven to be environmentally friendly, affordable, easy to make, and economically promising. This activity supports higher education performance indicators and the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program. In conclusion, the community is capable of independently managing agricultural waste into valuable products. Continued mentoring and product marketing development are recommended to ensure long-term sustainability.